2011
DOI: 10.1152/ajplung.00128.2010
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of PPARγ reverses lipid accumulation in alveolar macrophages of GM-CSF knockout mice

Abstract: -Pulmonary alveolar proteinosis (PAP) is a lung disease characterized by a deficiency of functional granulocyte macrophage colony-stimulating factor (GM-CSF) resulting in surfactant accumulation and lipidengorged alveolar macrophages. GM-CSF is a positive regulator of PPAR␥ that is constitutively expressed in healthy alveolar macrophages. We previously reported decreased PPAR␥ and ATP-binding cassette transporter G1 (ABCG1) levels in alveolar macrophages from PAP patients and GM-CSF knockout (KO) mice, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 39 publications
0
40
0
1
Order By: Relevance
“…By its action on alveolar macrophages it significantly contributes to surfactant homeostasis (149,166). Recently, several publications highlighted GM-CSF to be highly protective in different preclinical models of ALI, including K. pneumoniae infection, influenza virus pneumonia, LPS-induced lung injury, and others (190).…”
Section: Putative Candidates For Treatment Of Alimentioning
confidence: 99%
“…By its action on alveolar macrophages it significantly contributes to surfactant homeostasis (149,166). Recently, several publications highlighted GM-CSF to be highly protective in different preclinical models of ALI, including K. pneumoniae infection, influenza virus pneumonia, LPS-induced lung injury, and others (190).…”
Section: Putative Candidates For Treatment Of Alimentioning
confidence: 99%
“…Nonetheless, a study has demonstrated that PPARg overexpression in GM-CSF-knockout lung macrophages, which are deficient in PPARg expression, rescues alveolar surfactant accumulation, indicating potential regulation of PPARg expression by GM-CSF signaling. 62 It is, therefore, possible that acquired downregulation of other GM-CSF signaling pathways may be involved in the pathogenesis. The association between increased IFN-g and reduced PPARg has been described.…”
Section: Blood 8 January 2015 X Volume 125 Number 2 Aberrant T Cellmentioning
confidence: 99%
“…The AM accretion of lipid is attributed to compromised catabolic capacity (10) and affected signalling cascade(s) downstream of GM-CSF involving PPARγ have been extensively characterised (14,15). cells increases alveolar surfactant but leads to a neutral lipid accumulation in AT2 cells (17).…”
mentioning
confidence: 99%